Pers Mengawal Demokrasi Daerah: Analisis Pemberitaan Implementasi Dana Keistimewaan di Harian Tribun Jogja - Indrakrista, Niti Bayu (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2015)
This paper examines the role of local press as institution that supports democracy in regional level, in decentralisation era. As an entry point, this paper uses the media coverage of Dana Keistimewaan in Tribun Jogja daily newspaper, a non-partisan press institution that established at post New Order era. Using Robert Entmanâs framing analysis, this research argues that consolidation of democracy has not yet fully embedded at regional level. Local press pays too many attention on technocratic administrative aspects, rather than democratic ones that may involve contribution of the people.